Semantic and Linguocultural Characteristics of Phraseological Units (In the Example of Uzbek and English Languages - Narmuratov Zayniddin Radjabovich (Web of Journals Publishing, 2023)
The article is devoted to the study of semantic and linguocultural characteristics of phraseological units in English and Uzbek languages. Etymological and cultural features of phraseological units are considered on the example of Uzbek and English languages.
Keywords: phraseological units, semantic field, linguistic and cultural analysis.